Elevated red cell distribution width predicts residual dizziness in patients with benign paroxysmal positional vertigo - Xie, Ke-Hang; Chen, Li-Chun; Liu, Ling-Ling; Su, Chu-Yin; Li, Hua; Liu, Run-Ni; Chen, Qing-Qing; He, Jia-Sheng; Ruan, Yong-Kun; He, Wang-Kai (Frontiers in Neurology, 2022)
Objective: The present study aims to determine whether residual dizziness (RD) after successful repositioning treatment in benign paroxysmal positional vertigo (BPPV) patients could be predicted by red blood cell distribution width (RDW). Material and methods: In this study, a total of 303 BBPV patients hospitalized at the neurology department were investigated. The enrolled patients were divided into 2 groups after successful repositioning treatment: non-RD group included patients who were completely cured, RD group included patients with RD. We collected data on all subjects, including general information, blood routine examination, blood biochemical examination and magnetic resonance imaging tests. Results: The mean RDW values of patients in the RD group were significantly higher than that in non-RD group (13.63 ± 1.8 vs 12.5 ± 0.8; p < 0.000). In subsequent multivariate analysis, elevated RDW levels were a statistically significant risk factor associated with the occurrence of RD(odds ratio = 2.62, 95% confidence interval 1.88 – 3.64, p = 0.000).The area under the ROC curve was 0.72 in terms of its predictive ability to distinguish patients with RD. A cut-off point of 12.95% of RDW predicted RD with a sensitivity of 75.6% and a specificity of 69.5%. Conclusions: Elevated RDW level was related to increased risk of RD among BPPV patients, requiring further efforts to clarify the actual underlying pathophysiology.